Geometrical optimisation of a scroll compressor - Han, Wan Yi. (2009)
This project involved analytical studies attempting to search for combination of best design dimensions for scroll compressors having optimum performance with respect to power consumption. The work commenced with an assessment of physical aspects of the compressor using a mathematical model. It was found that the model could be used in predicting performance characteristics of the compressor.